2022
DOI: 10.2427/13123
|View full text |Cite
|
Sign up to set email alerts
|

QuantiFERON-TB Gold Plus evaluation for latent tuberculosis infection among Italian healthcare workers: a cross-sectional study

Abstract: Background: healthcare workers (HCWs) are at higher risk of being exposed to tuberculosis (TB). The aim of this study was to estimate LTBI prevalence and evaluate associated risk factors among Italian HCWs using a new generation IGRA test, Quantiferon Plus (QTF-Plus), providing also an analytical evaluation of this test. Methods: this cross-sectional study was conducted during the annual health surveillance program performed in 2017, evaluating 1470 HCWs of a teaching hospital in Rome, tested with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
3
1
0
Order By: Relevance
“…With regard to primary prevention of LTBI through vaccination, no evidence was found about the protective role of BCG vaccination, given that no significant differences were found among HCWs BCG vaccinated compared to unvaccinated. Our finding is in agreement with other studies [10,12,24] conducted among HCWs working in countries with low incidence of TB.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…With regard to primary prevention of LTBI through vaccination, no evidence was found about the protective role of BCG vaccination, given that no significant differences were found among HCWs BCG vaccinated compared to unvaccinated. Our finding is in agreement with other studies [10,12,24] conducted among HCWs working in countries with low incidence of TB.…”
Section: Discussionsupporting
confidence: 94%
“…In our study the prevalence of LTBI among HCWs was lower compared to data of other studies performed in healthcare settings in low TB incidence countries [1,13,18] and consistent with the findings of Coppeta et al [10,12]. HCWs aged ≥ 40 years were found at higher risk of LTBI; consistently with this finding and with the review performed by da Silva et al [21], an increased OR for LTBI was found in HCWs with length of service ≥ 15 years compared to low-experienced HCWs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations